Aberrant expression of long noncoding RNA TMEVPG1 in patients with primary immune thrombocytopenia. (2nd October 2016) - Li, Huiyuan; Hao, Yating; Zhang, Donglei; Fu, Rongfeng; Liu, Wenjie; Zhang, Xian; Xue, Feng; Yang, Renchi
Abstract: TMEVPG1 is a long noncoding RNA, which can promote Interferon gamma (IFNG) transcript as an enhancer. It has been reported that plasma IFNG concentration was elevated and partly due to dysregulation of micro RNAs in patients with primary immune thrombocytopenia (ITP). However, the effect of long noncoding RNA on IFNG expression in ITP is currently not well understood. To explore whether TMEVPG1 is involved in ITP, this study examined the TMEVPG1 expression and analyzed the association between TMEVPG1 transcript and IFNG expression in patients with ITP and healthy controls. The result showed that TMEVPG1 expression in peripheral blood mononuclear cells (PBMCs) from active ITP patients were lower than in that of healthy controls. Further activation for 24 h in vitro resulted in decreased TMEVPG1 while elevated IFNG mRNA and protein expressions in activated PBMCs compared with un-activated PBMCs both in ITP patients and healthy controls. However, TMEVPG1 and IFNG mRNA had same up-regulated tendency after short-time activation (1, 2 and 4 h) in healthy controls. In addition, we detected T helper 1 (Th1) cell associated transcription factors T-bet, STAT1 and STAT4 mRNA levels, and found T-bet mRNA expression was lower in PBMCs from ITP patient in remission compared with healthy controls. In conclusion, we speculated that TMEVPG1 could promote IFNG transcription, and IFNG over-expression negative feedback regulated on TMEVPG1 expression, which resulted in decreased TMEVPG1 in ITP patients.